Sunipia quangdangii, new orchid species (Orchidaceae) from southern Vietnam - Nguyen, van Canh; Averyanov, Leonid; Hoang, Nghia Son; Dang, van Son; Truong, Ba Vuong (Phytotaxa, 2020)
Sunipia quangdangii (Orchidaceae) discovered in southern Vietnam (Lam Dong Province, Da Lat City area) is described and illustrated as a new species for science. It is most close to S. pallida but differs in smooth petals, saccate hypochile with erose margin, small triangular side lobes and terete epichile. The new species is also similar to S. andersonii but differs in big size of plant, pseudobulbs and flower, short inflorescence scape and terete epichile shorter than hypochile. The flower of newly discovered plant somewhat resembles to flower of S. saccata, but new species strikingly differs in plant habit and short, 2-flowered inflorescence.